Enchytraeidae (Annelida: Oligochaeta) from Uzbekistan, with the description of a new species - Degtyarev, Maxim I.; Zvychaynaya, Elena Y.; Tarasyan, Karina K.; Gongalsky, Konstantin B. (Zootaxa, 2025)
The first list of terrestrial enchytraeids of Uzbekistan is provided, which includes 8 species belonging to 4 genera. A new enchytraeid species in the genus Fridericia Michaelsen, 1889, Fridericia korobushkini sp. nov., is described. It clearly differs from other species of the genus by max. 5 chaetae per bundle, presence of a subneural gland in XIV, 5 pairs of preclitellar nephridia, preclitellar chylus cells, and spermathecae with 2–4 diverticula of irregular shape, and without ectal glands.